POLITICAL PARTICIPATION OF GETASAN COMMUNITY IN SEMARANG REGENCY ELECTIONS IN 2015 - Mediatati, Nani; Nababan, Kristina Roseven (Humaniora, 2019)
This research aimed to describe the form and the level of political participation of the Getasan district community in the election of Semarang Regency in 2015. Data collection techniques were through interviews, observations, and document studies. Sample research amounted to 182 respondents that were taken from 13 villages in the district of Getasan, and each village was taken 14 respondents. While secondary data of literature studies and studies of documents were both derived from the contestants, the general election commission district, the mass media, and other relevant sources. There were two candidates for the regent and vice-regent period 2015-2020; they were Mundjirin with Ngesti Nugraha that supported by three political parties, and the second, Nur Jatmiko with Mas?ud Ridwan that supported by four political parties. The results show that the form of political participation in the community of Getasan in the election year 2015 can be listed into nine activities, such as participation in one of the political parties, the committee of elections, socialization the candidate, campaign, become a victory team participated in the procurement of polling stations, participated in the voting, participated in the security voting in polling stations, and participated in the process calculation of the vote.